The Inflation Theory in the Perspective of Al-Maqrīzī's Thought and it’s Implications in the Modern Economic World - Syarifah Siregar; Nurmiana Nurmiana; Riza Husnila Sari; Maidar Darwis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine the theory of inflation according to al-Maqrīzī and ways to overcome it and determine the differences in inflation theory according to al-Maqrīzī with modern economics. Data collection techniques are used by collecting his works both personally and jointly and are traced by other people's work on figures as secondary data. Analysis of the data used is content analysis. This research shows that inflation is a natural phenomenon that afflicts the lives of people throughout the world from the past until now. Inflation will occur when prices generally increase and continue. The way to deal with inflation is to overcome it by eliminating the causes of inflation such as corruption, excessive taxation, and the creation of excessive currency. He emphasized the use of dinars and dirhams in dealing with inflation. Al-Maqrīzī thought is not inferior to those of Western economists from the 19th Century and 20th Century.